Gama Is Thee! - Mullen, Stanley, 1911-1974 (Salt Lake City, UT : Project Gutenberg, 2021)
"Gama Is Thee!" by Stanley Mullen is a science fiction novel written in the early 1950s, during a time when speculative fiction was exploring themes of identity, mutation, and the unknown. The book follows an intriguing premise set on Venus, where the mysterious Khaljean operates a fantastical zoo that houses various bizarre creatures. The story revolves around themes of adventure, survival, and the motivations of its characters in a richly imagined extraterrestrial landscape. The narrative unfolds through the experiences of several characters, including Bat Ferris, a fugitive gamma-man, and Pao Chung, a cunning businessman involved in illegal activities on Venus. They team up with Bogus Angel, a mutant with the unusual ability of flight, and Khaljean's daughter, Teucrete, as they attempt to escape from the law after a chaotic jailbreak. As they navigate a dangerous world filled with monstrous creatures and the threat of capture, they uncover Khaljean's secret past and the larger implications of a hidden alien influence over humanity. Tensions rise through violent confrontations and shifting alliances, culminating in their quest to find and destroy a mysterious force believed to warp the minds of men. Through adventure and deception, the story explores deep moral questions about power, survival, and the implications of genetic mutation, set against a backdrop of vivid world-building. (This is an automatically generated summary.)
Release date is 2021-01-16
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Adventure stories; Venus (Planet) -- Fiction; Escaped prisoners -- Fiction